Kecemasan, Pelayanan Kebidanan, dan Pemberian Informasi tentang Virus Corona (COVID-19) oleh Bidan di Wilayah Madura - Eny Susanti; Zakkiyatus Zainiyah (Media Kesehatan Masyarakat Indonesia, 2020)
The incidence of the COVID-19 pandemic is very important to know because it has a psychological impact on the coronavirus pandemic incident on health workers. The outbreak of the COVID-19 epidemic has caused high levels of stress from health workers and increased illness in the community. The research objectives were to determine midwife anxiety, the role of midwives in midwifery services, and to provide information about the coronavirus (COVID-19) to mothers and children in the Madura region. This type of research is descriptive, the population of this study was midwives in Madura with a total sample of 123 midwives. Data collection uses the Google Form system which is distributed to all midwives in the Madura region. The collected data were analyzed using frequency distribution tables. The results showed that midwives experienced severe anxiety by 16.3%, 17.9% very severe anxiety, and 22.8% moderate anxiety, midwives also provided good midwifery services at 87.0% and provided information about the prevention of coronavirus transmission properly by midwives by 77.2%. This pandemic has had a huge impact on the provision of midwifery services, especially programs that have been implemented routinely so that the program cannot be implemented and midwives also experience anxiety because they are the spearhead in midwifery services. It is hoped that there will be good cooperation between patients and midwives, especially patients, to continue to follow the principles of preventing transmission of the coronavirus and to provide good and correct information to patients, especially when coming from out of town.